Elucidating deep-sea thermometric deviations and their consequences for oceanic heat content assessment via high-pressure calibration - Muzi Zhang; Muzi Zhang; Qingquan Sun; Qingquan Sun; Xiaoxue Bai; Xiaoxue Bai; Chi Wu; Chi Wu; Chi Wu (Frontiers in Marine Science)
This paper extensively investigates the performance of the representative SBE 3 deep-sea thermometer (Sea-Bird Scientific) under various stepwise pressure conditions. A high-precision pressure-temperature vessel was employed to simulate deep sea environments, conducting systematic pressure experiments with precise temperature control (0.5 mK) across a temperature range of -2 to 35°C and from atmospheric pressure to full ocean depth (0–12700 m). A Standard platinum resistance thermometer (SPRT), isolated from the pressure environment and placed adjacent to the SBE 3, served as a calibration reference throughout the experiments. The drift of the SBE 3, reaching up to 10 mK in this study, was meticulously quantified at varying pressures and temperatures. Subsequently, a linear calibration method was developed, ensuring that the thermometer maintained an accuracy of ±0.0005°C (± 0.5 mK) across all tested high-pressure conditions, including a maximum pressure of 1050 bar. Crucially, this study discusses the negative impact of pressure-induced temperature errors on the estimation of ocean heat content in the Pacific, emphasizing the importance of conducting high-pressure calibration tests before and after oceanographic deployments. These measures are vital for ensuring the accuracy of deep-sea temperature measurements, which are critical for understanding global climate dynamics and improving the calibration of deep-sea sensors.